Effective Communication in Increasing Parental Involvement in Children's Education in Klambir V Kebun - Nurhalima Tambunan (Yayasan Multidimensi Kreatif, 2024)
The purpose of this research is to provide knowledge to parents about the importance of good communication with children. This type of research is qualitative research that is descriptive in nature data collection techniques through observation, interviews and documentation. The data sources in this study are village heads, community leaders and parents. This paper seeks to explain that effective communication between parents and children not only increases parental involvement in children's education but also has a positive impact on children's cognitive and emotional development. By building good communication, parents can act as active educational partners, creating an optimal learning environment for their children. This includes communicating effectively, listening empathetically, and understanding the child's emotional needs. With a better understanding, parents are expected to play an active role in their children's education. Encourage parents to be actively involved in the child's education process, both at home and at school. This includes attending school meetings, supporting learning activities at home, and collaborating with teachers to monitor children's academic development. building a strong communication network between parents, teachers, and the school. With good communication, all parties can share information and support each other in an effort to improve the quality of children's education.